An overview of thermochemical modelling of CANDU fuel and applications to the nuclear industry. (December 2016) - Corcoran, E.C.; Kaye, M.H.; Piro, M.H.A.
Abstract: Thermodynamic models of complex chemical systems provide an elegant and cost effective means to predict chemical interactions of materials and to provide guidance to experimental research to minimise costs. Starting in 1995 at the Royal Military College of Canada, a thermodynamic treatment of irradiated nuclear fuel has been developed that not only describes the thermochemistry of the fuel at elevated temperatures during a potential Loss-of-Coolant Accident (LOCA), but it can also be used to help predict the oxidation environment for fresh fuel measurements, irradiated fuel behaviour, the aqueous chemistry of fuel debris in coolant, nuclear waste disposal, and other systems involving nuclear fuel. Furthermore, this treatment was supported by several experimental campaigns at the Canadian Nuclear Laboratories and the Institute of Transuranium Elements for validation purposes. This paper will trace the development of this treatment and demonstrate its current practice and future potential in the general context of performance and safety of nuclear fuel.